Contemporary African American Fiction : New Critical Essays - Williams, Dana A., 1972- (Book collections on Project MUSE., 2009)
In Contemporary African American Fiction: New Critical Essays, edited by Dana A. Williams, eight contributors examine trends and ideas which characterize African American fiction since 1970. They investigate many of the key inquiries which inform discussions about the condition of contemporary African American fiction. The range of queries is wide and varied. How does African American fiction represent the changing times in America and the world? How are these changes reflected in narrative strategies or in narrative content? How do contemporary fictionists engage diasporic Africanisms, or how do they renegotiate Americanism? What is the impact of cultural production, gender, sexuality, nationality, and ethnicity on this fiction? How does contemporary African American fiction reconstruct or rewrite earlier "classic" African American, American, or world literature? Authors under study include Ernest J. Gaines, Ishmael Reed, Edwidge Danticat, Octavia E. Butler, Olympia Vernon, Toni Morrison, and Reginald McKnight, among others. These essays remind us that the African American literary tradition is about survival and liberation. The tradition is similarly about probing, challenging, changing, and redirecting accepted ways of thinking to ensure the wellness and the freedom of its community cohorts. The essays identify new ways contemporary African American fiction continues the tradition's liberatory inclinations-they interrogate the ways in which antecedent texts and traditions influence contemporary texts to create new traditions.